Polyosma maliauensis - Hoo, P.K.; Tsen, S.; Colin Ruzelion Maycock (International Union for Conservation of Nature and Natural Resources, 2020)
Polyosma maliauensis is a small tree recorded only once from the Maliau Basin Conservation Area in Central Sabah. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are both 4 km2 and are not in decline. The area is a Totally Protected Area (TPA). The potential threat is climate change which may push the species towards a higher threat category or Extinct in the near future, as a warming climate will degrade the habitat of the species and potentially cause drought. Hence, it is assessed as Vulnerable. Polyosma maliauensis is endemic to Sabah, Malaysia. It is known only from the lower montane forest of the Maliau Basin Conservation Area, Sabah (Saw 2004).